HUBUNGAN ANTARA OBESITAS DENGAN RISIKO MENDERITA GANGGUAN TIDUR OBSTRUCTIVE SLEEP APNEA (OSA) PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Suryawan, Putu; Tirtayasa, Ketut (E-Jurnal Medika Udayana; vol 5 no 3(2016):e-jurnal medika udayana, 2016)
CORRELATION OF OBESITY WITH THE RISK LEVEL OF SUFFERING SLEEP DISORDER OBSTRUCTIVE SLEEP APNEA (OSA) WITHIN MEDICAL STUDENT IN FACULTY OF MEDICINE UDAYANA UNIVERSITY Obstructive Sleep Apnea (OSA) is sleep disorder with significant air flow reduction and cessation of breathing repeatedly with respiratory effort episodically. There are various factors that contribute to pathogenesis of OSA. Obesity is a major risk factor in development and progression of OSA. The increased prevalence of obesity is associated with an increased risk of suffering OSA. This studyaimed to determine the correlation between obesity and the risk of suffering sleep disorder OSA within medical student in Faculty of Medicine Udayana University. This study design was cross-sectional observational analitic study. Sample selection was total sampling method with total 473 respondents. The data were obtained using Berlin questionaire, Body Mass Index (BMI), and question of demographic characteristics. Descriptive characteristics respondents showed 179 (37.8%) male and 294 (62.2%) women, with majority age was 19 years (36.4%) and median BMI 21.007 (15.61-40.0). The prevalence of OSA risk obtained 30 respondents (6.3%) included into high risk, 21 men and 9 women, and 443 respondents (93.7%) included into  low risk. The prevalence of the Obese in high risk category was24 (80.0%) respondents that greater than the Not Obese in high risk categoriy was6 respondents (20.0%). Differences of proportion was performed bivariate analysis by chi-squre, resulted p value 0.00 (p <0.05) with Spearman correlation value was 0.407. We concluded that there was a significant correlation between obesity with the risk level of suffering OSAwithin medical studentin Faculty of Medicine Udayana universitywith prevalence ratio (RP) 23.262 (95% -CI: 9.155 to 59.104).
Keywords: obesity, OSA risk, medical student